On the generalized convolution for Fc, Fs, and K–L integral transforms - Virchenko, N.O.; Thao, N.X. (Український математичний журнал, 2012)
We study new generalized convolutions with weight function for the Fourier cosine, Fourier sine, and Kontorovich – Lebedev integral transforms in weighted function spaces with two parameters. These generalized convolutions satisfy the factorization equalities.